Structural conformation of lysozyme layers at the air/water interface studied by neutron reflection - Lu, JR; Su, T; Thomas, R; Penfold, J; Webster, J (1998)
The adsorption of chicken egg white lysozyme at the air/water interface has been studied by specular neutron reflection. The variation of the total thickness of the lysozyme layer at the surface of water under varying solution conditions has been determined. The use of mixed H2O and D2O allowed the determination of the extent of immersion of the layer in water at all concentrations. The measured layer thickness combined with the globular dimensions of lysozyme suggests that the adsorbed lysozyme molecules retain their globular structure with no significant denaturation. Measurements were made over a lysozyme concentration range of 9 × 10-4g dm-3 to 4 g dm-3 at pH 7 and at an ionic strength of 0.02 M. The thickness of the layer was determined by measuring neutron reflectivities in null reflecting water (NRW) where the signal is only from the adsorbed protein layer. Below 0.1 g dm-3 the surface coverage increases with bulk concentration but the thickness of the layer is constant at 30 ± 3 Å, suggesting that lysozyme is adsorbed sideways-on. As the bulk concentration increases, the layer thickness gradually increases to a value of 47 ± 3 Å2 at a bulk concentration of 1 g dm-3, suggesting that the molecules switch from sideways-on to longways-on orientations. The area per molecule at 1 g dm-3 was found to be 950 ± 50 Å2 which is close to the limit of 30 × 30 Å2 for a saturated layer of longways-on molecules. The extent of mixing of the layer with water was determined directly by measuring reflectivity profiles in mixed H2O and D2O. A two layer model was found to be appropriate with an upper layer in air and a lower layer fully immersed in water. The thickness of the layer in air was found to vary from 15 ± 5 Å at the lowest bulk concentration to 9 ± 3 Å at the highest concentration studied. The results show that as the total layer thickness increases with bulk concentration the fraction of the layer immersed in water increases from 50 to 85%. At the highest concentration of 4 g dm-3 the adsorbed layer is better described by a two layer model consisting of a close packed top layer of thickness 47 ± 3 Å and a loosely packed sublayer of 30 ± 3 Å.